Main Reasons for the Transformation of Mandatory Hungarian Private Pension Funds - Peter Novoszath (Central European Public Administration Review)
The main purpose of writing this paper was to provide a clear summary of the main facts and motives of restructuring the financing of Hungarian social security system which has been in process since 2010. One of the main lessons learned from the development of the Hungarian pension system so far is that the mandatory private pension funds working on the basis of a funded scheme were not able to solve the problems whose solution they were established for. In addition, they caused further problems.